KAJIAN EFISIENSI TERMAL DARI BOILER DI PEMBANGKIT LISTRIK TENAGA UAP AMURANG UNIT 1 - Hanzen Yauri Kurniawan; Hardi Gunawan; Benny Maluegha (JURNAL POROS TEKNIK MESIN UNSRAT, 2015)
ABSTRACT Indonesia has a considerably high potential resources that can be harnessed to generate electricity through power plants. At Amurang Steam Power Plant (PLTU Amurang), coal is used for the fuel and boiler is the equipment to burn the coal producing heat. Boiler is one of the equipments in the thermodynamics cycle which aims to turn the water into steam. This study was conducted to determine the thermal efficiency of the boiler in PLTU Amurang Unit 1 based on operational data. The data collected from the PLTU Amurang . The data is then used to calculate the thermal efficiency of the boiler. Calculations using the direct method and the indirect method. The calculations shows boiler thermal efficiency is 91.73% and 92.33% respectively. When compared with the thermal efficiency of the boiler according to specifications then the difference is 0,41% and 0,19%. Â  Key Word: Boiler and Thermal Efficiency